Incidence of venous thromboembolism and association with PD-L1 expression in advanced non-small cell lung cancer patients treated with first-line chemo-immunotherapy - Liliana Aguiar De Azevedo; Charles Orione; Cécile Tromeur; Francis Couturaud; Renaud Descourt; Margaux Geier (Frontiers in Oncology, 2024)
BackgroundVenous thromboembolism (VTE) is a serious complication in non-small cell lung cancer (NSCLC) patients. The use of thromboprophylactic therapy is subject to an accurate assessment of the VTE risk depending on patients, tumor characteristics and type of systemic antineoplastic treatments. However, little is known concerning the risk of VTE in patients suffering from an advanced NSCLC treated with first-line chemo-immunotherapy and the impact of tumor biomarkers such as PD-L1 expression.MethodsWe performed a retrospective, observational, single-centre study in a cohort of advanced NSCLC patients treated with first-line chemo-immunotherapy. The primary endpoint was the incidence of VTE. Secondary endpoints were the cumulative incidence of VTE, the impact of PD-L1 on VTE occurrence, overall survival, the rate of VTE recurrence under anticoagulant treatment and the rate of bleeding complications.Results109 patients were included, of whom 21 (19.3%) presented a VTE event during a median follow-up of 13 months. VTE incidence at 3, 6 and 12 months was 12.1%, 15.1% and 17.5% respectively. 61% were pulmonary embolisms, 9.5% were isolated deep vein thrombosis and 14.3% were central venous catheter-related thrombosis. Our study did not show a significant impact of PD-L1 on VTE occurrence. Overall survival at 6, 12 and 24 months was 81.9%, 74.4% and 70.3% respectively. Four patients developed a recurrent VTE under anticoagulation therapy 3 to 5 months after the first VTE event. One patient suffered from a major bleeding complication while under anticoagulation therapy, leading to death.ConclusionVTE is a common complication in advanced NSCLC patients treated with concomitant chemo-immunotherapy. In our study, 19.3% of patients developed a VTE during a median follow-up of 13 months. PD-L1 did not appear to be associated with VTE occurrence. We recorded high VTE recurrence rates despite anticoagulant treatment. Further investigations are needed to determine if high PD-L1 expression is associated with VTE.